Vaalbara Palaeomagnetism - Evans,ME; Muxworthy,AR (Canadian Journal of Earth Sciences, 2018)
Vaalbara is the name given to a proposed configuration of continental blocks—the Kaapvaal craton (southern Africa) and the Pilbara craton (north-western Australia)—thought to be the Earth’s oldest supercraton assemblage. Its temporal history is poorly defined, but it has been suggested that it was stable for at least 400 million years, between 3.1 and 2.7 Ga. Here, we present an updated analysis that shows that the existence of a single supercraton between ∼2.9 and ∼2.7 Ga is inconsistent with the available palaeomagnetic data.